Age is not a limit at AeU. - The, Star (The STAR, 2014)
Yeop Ali Mohd Dobi prefers to pursue Doctorate in Business Adminstration at Asia e University (AeU). He is 73 years old.- World class supervision - creating your learning environment - the worlds research at your fingertips.